Peningkatan Hasil Belajar Sosiologi Tema Perubahan Sosial dan Dampaknya terhadap Kehidupan Masyarakat dengan Metode Discovery Learning Siswa Kelas XII IPS 2 SMAN 6 Metro - Wianta, I Made (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This research aims to improve the sociology learning outcomes of students in class discovery learning, 2) Can the discovery learning method improve the learning outcomes of XII IPS 2 students at SMAN 6 Metro in learning sociology. The method used is test techniques and non-test techniques. The results of the research showed that learning outcomes increased from the average pre-cycle results of 59.42%, cycle I to 73.57%. Cycle II became 82.50%, cycle III increased to 86.07%. Learning completeness in the pre-cycle was 17.85%, in cycle I it increased to 42.87%, cycle II became 85.71% and cycle III increased to 100%.